2019
DOI: 10.24287/1726-1708-2019-18-4-109-117
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic features of pediatric gliomas

Abstract: Gliomas are the most common central nervous system tumors demonstrating an extremely broad range of clinical behavior. Over last few decades the understanding of molecular genetic mechanisms of tumor initiation and progression increased significantly. Furthermore, the identification of prognostic and predictive biomarkers aids the development of personalized and risk-adapted therapeutic approaches. In this review, we summarize the molecular findings in pediatric gliomas, both low and high grade (LGG and HGG), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
1
0
3
Order By: Relevance
“…По данным A. Johnson и соавт., в серии из 90 ГБ аберрации H3F3A наблюдались в 43 (48 %) случаях, из них H3 K28M -в 35 (81 %), H3 G35R -в 8 (19 %) [2]. Кроме того, в исследованиях, посвященных изучению молекулярно-генетического профиля ВЗГ, подчеркивается, что для замен K28M и G35R / V харак терна корреляция с локализацией опухоли [2,3]. В глиомах срединных структур выявляется мутация H3 K28M, в глиомах полушарной локализации -H3 G35R / V. Данная особенность подтверждена и в серии наших наблюдений.…”
Section: экспериментальные статьиunclassified
See 2 more Smart Citations
“…По данным A. Johnson и соавт., в серии из 90 ГБ аберрации H3F3A наблюдались в 43 (48 %) случаях, из них H3 K28M -в 35 (81 %), H3 G35R -в 8 (19 %) [2]. Кроме того, в исследованиях, посвященных изучению молекулярно-генетического профиля ВЗГ, подчеркивается, что для замен K28M и G35R / V харак терна корреляция с локализацией опухоли [2,3]. В глиомах срединных структур выявляется мутация H3 K28M, в глиомах полушарной локализации -H3 G35R / V. Данная особенность подтверждена и в серии наших наблюдений.…”
Section: экспериментальные статьиunclassified
“…Стоит отметить, что в зависимости от локализации точки разрыва могут возникать различные типы химерного гена ETV6-NTRK3. Вариант химерного транскрипта ETV6 (экзон 4) -NTRK3 (экзон 14) у детей с ВЗГ встречается заметно чаще [3,4,19].…”
Section: экспериментальные статьиunclassified
See 1 more Smart Citation
“…Further studies of molecular landscapes of high-grade gliomas confirmed the high prevalence of H3 K27M variant in diffuse midline gliomas (DMG). This variant is observed in up to 94% of diffuse brainstem gliomas, 65% of thalamic gliomas, and 60% of spinal cord gliomas [ 4 ]. Moreover, the presence of H3 K27M mutation is a very unfavorable prognostic factor.…”
Section: Introductionmentioning
confidence: 99%